A Review of Business Process Management using four SAP implementations at Smithfield Foods Company (Global Journal of Management and Business Research, 2020)
The business process of a company signifies the fundamental wealth and operation. A business process contains a straight influence on the products and services alluring the market. The business process describes the way of utilizing the resources to complete customer arbitrary products and services. The series of operations, events, activities, and decisions is categorized as a business process. Business Process Management (BPM) is the way of recognizing the manner of performing the work to gain outcomes and to acquire the benefits from enhanced opportunities in a company. BPM is not only to perform better operations in separate activities. Specifically, it is about managing the plenary series of operations, events, activities, and decisions that eventually annex value to the company and its customers.
Keywords: business and IT configuration; business process reengineering; sap implementation